Zavrelia parapentatoma (Chironomidae: Diptera), a curious new species from North America, revealed by molecular methods - Namayandeh, Armin; Hudson, Patrick L.; Ghaderi, Edris; Stott, Wendylee (Zootaxa, 2023)
In this study, we describe Zavrelia parapentatoma sp. nov. based on specimens collected near a cattail marsh in Michigan, USA. At first glance, the new species resembles Zavrelia pentatoma Kieffer & Bause, 1913 closely. However, a detailed morphological and molecular assessment revealed the differences. Morphologically the two species can be separated mainly based on the shape and pattern of long spinulae between long anal crests of adult males and setal patterns on the pupal abdomen. Larvae of both species also have some subtle morphological differences that are discussed in this study. Our molecular analysis of cytochrome oxidase (COI) genes and methods for delimiting species further supported the presence of a new species. In this study, we describe all the life stages, provide life history observations for this new species, and provide keys to adult males and immatures of the genus Zavrelia.